DUKUNGAN SOSIAL SUAMI TERHADAP KEBERHASILAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PASIR JAYA KABUPATEN TANGERANG - Febi Ratnasari; Maya Febriana (Universitas Yatsi Madani, 2017)
One of the government's efforts in reducing infant mortality rate is by increasing exclusive breastfeeding in infants. Feeding for babies can be achieved by creating understanding and support from the environment so that mothers can breastfeed exclusively. This study aims to determine whether there is a relationship between husband's social support with the success of exclusive breastfeeding in the work area of ​​Pasir Jaya Puskesmas Distritc of Tangerang In 2017. The research method used is an analytical survey with retrospective approach, the research that seeks to look backward looking, data collection started from the effects that have occurred. The sample technique used by researchers is non-random sampling technique in quota and accidental sampling with the number of samples was 179 respondents. Data analysis techniques used univariate and bivariate analysis. The result of chi square test is 1,000> 0,05. Ha is rejected (p> 0,05) meaning that there is no relationship between husband's social support with exclusive breastfeeding success in work area of Pasir Jaya Puskesmas District of ​​Tangerang in 2017. Researchers advise family members, especially husbands, to participate in exclusive breastfeeding by providing social support during exclusive breastfeeding mothers up to six months of age and eliminating a culture of supplementary feeding other than breastmilk before the infant is six months old.